Uso da Inteligência Artificial Generativa na Iniciação Científica: um exercício de design especulativo - Braz, Matheus Petroni (2024)
The application of Generative Artificial Intelligence (GenAI) tools is transforming various sectors of society, including science. These tools have already proven useful in tasks such as reference searching, academic writing, project formatting, precise translations and data analysis. Even the generation of new research perspectives and hypotheses is possible if done with some caution. However, despite the promising expectations, there are many challenges associated with their use, especially for young researchers at the beginning of their careers. Seeking to center the academic community in this debate, this research identified the main expectations and concerns of university students engaged in Scientific Initiation projects and supervising professors regarding the use of GenAI in academic research. The combination of semi-structured interviews with the use of Speculative Design artifacts revealed that, although there is undeniable recognition of the advancement of this technology and its effective use for more routine project tasks like data gathering, reference searching and writing support, both students and professors refuse that its current development stage allows for broader use in scientific applications. Special concerns are raised about its impact on the job market, the development of critical and original thinking, the reliability of the data obtained and copyright issues. There is even bigger resistance to this use among students than among professors. The results demonstrate that new teaching strategies in science are necessary, which include the use of this technology in a way that emphasizes the need for supervision, result verification and ethical considerations, while maintaining the importance of critical thinking and interpersonal relationships in scientific development